Geolocation assessment for CrIS sensor data records. Issue 22 (26th November 2013) - Wang, Likun; Tremblay, Denis A.; Han, Yong; Esplin, Mark; Hagan, Denise E.; Predina, Joe; Suwinski, Lawrence; Jin, Xin; Chen, Yong
<x xml:space="preserve">Abstract</x> [1] As important as spectral and radiometric calibration, the geometric calibration is one of the requisites for the Suomi National Polar‐Orbiting Partnership Cross‐track Infrared Sounder (CrIS) Sensor Data Records (SDR). In this study, spatially collocated measurements from the Visible Infrared Imaging Radiometer Suite (VIIRS) band I5 are used to evaluate the geolocation performance of the CrIS SDR by taking advantage of high spatial resolution and accurate geolocation of VIIRS measurements. The basic idea is to find the best collocation position between VIIRS and CrIS measurements by shifting VIIRS images in the track and scan directions. The retrieved best collocation position is then used to evaluate the CrIS geolocation performance by assuming the VIIRS geolocation as a reference. Sensitivity tests show that the method can well detect geolocation errors of CrIS within 30° scan angle. When the method was applied to evaluate the geolocation performance of the CrIS SDR, geolocation errors that were caused by software coding errors were successfully identified. After this error was corrected and the engineering packets V35 were released, the geolocation accuracy is 0.347 ± 0.051 km (1σ) in the scan direction and 0.219 ± 0.073 km in the track direction at nadir.